ANALISIS HARGA MINYAK SAWIT, TINJAUAN KOINTEGRASI HARGA MINYAK NABATI DAN MINYAK BUMI - M. Efendi Arianto; Arief Daryanto; Bustanul Arifin; Nunung Nuryartono (Jurnal Manajemen & Agribisnis, 2010)
The purpose of this study was to gain better understanding on  vegetable oils and crude oil relationship. Dynamic relationship among vegetable oils and crude oil is investigated using vector error correction model (VECM). The data is monthly price data from January 1980 to December 2008, consist of price of the most produced vegetable oils, i.e. palm oil, soyabean oil and rapeseed oil. Crude oil price (CPO) was taken into account since biodiesel converted from vegetable oils has become an important alternative of fuel. To get picture of dynamic interrelationship among vegetable oils and crude oil during commodity price soar period, this study was divided into period of investigation, which is period 1980-2003 (before commodity price soar) and period 2004-2008 (during commodity price soar).  This study indicates that there is cointegration between vegetable oils and crude oil, and vegetable oils were influenced by crude oil especially in commodity price soar period.